Aerosol-Precipitation Interactions over India: Review and Future Perspectives - S. Ramachandran; S. Kedia (Advances in Meteorology)
Atmospheric aerosols can interact with clouds and influence the hydrological cycle by acting as cloud condensation nuclei. The current study reviews the results obtained on aerosol-precipitation interactions over India and the surrounding oceanic regions. An analysis of aerosol and cloud characteristics over the Arabian Sea, India, and the Bay of Bengal during summer monsoon in the last decade reveals large regional, intraseasonal, and interannual variations. Aerosol optical depth (AOD) and aerosol absorbing index (AAI) in 2002 (a drought year) are higher over India when compared to normal monsoon years. Cloud effective radius (CER) and cloud optical thickness exhibit a negative correlation with AOD over India, which agrees well with the indirect radiative effects of aerosols. Over Bay of Bengal CER is positively correlated with AOD suggesting an inverse aerosol indirect effect. In future, observatories to measure aerosol characteristics (amount, size, type, chemical composition, mixing, vertical and horizontal distributions), and cloud properties (number and size) over several locations in India, and intense observational campaigns involving aircraft and ships are crucial to unravel the quantitative impact that aerosols have on Indian monsoon. Satellite remote sensing of aerosol distribution, their chemical composition, microphysical properties of clouds, solar irradiance, and terrestrial longwave radiation is important.